SLE presenting as migratory arthritis, chorea and nephritis - Ajmani, Sajal (Mediterr J Rheumatol, 2018)
We present a case of a 12-year-old girl who presented with migratory arthritis, chorea and ascites. She was diagnosed to have systemic lupus erythematosus (SLE) and subsequently responded to immunosuppressive therapy. She had been misdiagnosed earlier as having rheumatic fever. Our case highlights the fact that SLE should be considered in the differential diagnosis of a patient with migratory arthritis & chorea. Generally, chorea in SLE is immune-mediated rather than due to ischemia and has good prognosis.